REVIEW ON TAX AVOIDANCE WITH REPUTATED JOURNAL LITERATURE - Mohammad Tri Atmaja; Wiwik Supratiwi (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
Tax avoidance is a way to minimize payments made by companies. The existence of gray tax regulations can provide an opening for legal tax evasion. Tax avoidance practices are always followed by good governance, indicating that companies that have good governance will do tax avoidance effectively and efficiently. It is assumed that tax avoidance can affect stock prices and increase firm value. Researchers realize that tax avoidance is an important thing to develop research related to this matter. Where minimal tax avoidance research in Indonesia is very likely to be developed for further research. Researchers reviewed several existing journals, both journals from Sinta journals and from reputable journals Scopus